2015
DOI: 10.1093/rpd/ncv155
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced non-targeted effects: some open questions

Abstract: The existence of non-targeted effects (NTEs) of radiation (genomic instability and bystander effects) has been generally accepted for >20 y; however, there is research, which was largely ignored going back to 1915 reporting these effects. Despite today's general acceptance of the phenomenon of NTE, there is little agreement about the mechanisms involved and the implications in radiation biology and radiation protection. The aim of this review was to consider some of the odd data, which have been published in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…RIBE has been detected in vitro 36 , in 3D tissues 7 , and in mouse models 810 . Growing evidence shows that bystander responses can be regulated by two mechanisms—(i) gap junction intercellular communication (ii) communication of soluble factors released by irradiated cells or organs 11,12 . With respect to the soluble factors, Mothersill and Seymour first reported that the irradiated medium from human epithelial cell medium displayed a toxic effect on fibroblast cells 13 .…”
Section: Introductionmentioning
confidence: 99%
“…RIBE has been detected in vitro 36 , in 3D tissues 7 , and in mouse models 810 . Growing evidence shows that bystander responses can be regulated by two mechanisms—(i) gap junction intercellular communication (ii) communication of soluble factors released by irradiated cells or organs 11,12 . With respect to the soluble factors, Mothersill and Seymour first reported that the irradiated medium from human epithelial cell medium displayed a toxic effect on fibroblast cells 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers agree that reactive oxygen and/or nitrogen species are involved and that p53, cytokines, and stress response pathways such as Mitogen activated protein kinase (MAPK) are important. 13 15 Ion channels in both outer cell membranes and mitochondrial membranes appear to be involved. 16 19 More recently, a role of UV resulting from both excitation decay and exosomes has been identified, 20 23 and these are thought to contain miRNAs, although exosome profiling is at a very early stage.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive researches have focused on the health effects of IR in the hope of understanding the risk of IR exposure. In contrast to the traditional radiobiological viewpoint that the biological effects of IR are restricted to directly hit cells, the concept of radiation-induced bystander effects (RIBE) has updated our perception of the biological effects of IR [2]. It is realized that the existing radiotherapy models should be reconsidered due to the discovery of radiation-induced secondary carcinogenesis in distant organs after radiotherapy [3], as well as the carcinogenesis induced by low-dose/low-dose-rate (LD/LDR) radiations, for example, the astronauts exposed to LD/ LDR high atomic number (Z) and energy (HZE) space radiations [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is realized that the existing radiotherapy models should be reconsidered due to the discovery of radiation-induced secondary carcinogenesis in distant organs after radiotherapy [3], as well as the carcinogenesis induced by low-dose/low-dose-rate (LD/LDR) radiations, for example, the astronauts exposed to LD/ LDR high atomic number (Z) and energy (HZE) space radiations [4]. It is generally believed that both gap junctional intercellular communication (GJIC) and soluble factors generated by the irradiated cells are involved in the RIBE [2], of which transforming growth factor-β1 (TGF-β1) is a key soluble factors [5][6][7]. Although TGF-β1-related signaling pathways were studied extensively, the mechanisms underlying the TGF-β1-induced tumorigenesis remain unclear, especially its role in LD/LDR radiations-or RIBE-induced tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%